P18: MULTIPLE DIAGNOSIS OR CONTINUUM OF DISEASE. Issue 3 (March 2016) - Datla, S; Parker, K; Robert, L; Soloman, N
Abstract : Purpose of Study: Multicentric Castleman's disease (MCD) is a rare lymphoproliferative disorder characterized by peripheral lymphadenopathy (LAD), hepatosplenomegaly(HSM), and B symptoms. It is associated with HIV and HHV8 infection. We report a case of young woman presented with B symptoms, workup suggestive of lupus but lymph node biopsy (BX) was consistent with MCD. Association of SLE with MCD is rare. We report this case to increase awareness of this potential diagnostic and therapeutic dilemma. Methods Used: Patient is a 27 yr old black woman presented with malaise, fevers, cough, weight loss, arthralgia, alopecia, numbness of extremities and Raynaud's phenomenon. Patient had skin tightness around the mouth, telangiectasia, digital ulcers, HSM, pitting edema, diffuse LAD and moderate pericardial effusion. Laboratory results consistent with hemolytic anemia with Hb 5.6 g/dl, direct coombs positive, elevated reticulocyte count, LDH and low haptoglobin. Initial RF, ANA, and all infectious work up including HIV were normal. She was transfused cautiously, with inconclusive LN and bone marrow Bx. Patient left hospital against medical advice. She presented two days later with altered mental status (AMS) and hypotension. CT head and Lumbar puncture were negative. Hypotension responded to fluids, but no response in AMS. Repeat ANA, AntiSSB, AntiSm, AntiRNP, and Antihistone antibodies were positive. Patient met diagnostic criteria for SLE and was subsequently treated for lupus cerebritis with pulse steroids, with moderate improvement in mental status. Repeat LNBX revealed reactive lymphadenitis with features of MCD, HHV8 negative. Patient was treated with IL-6 inhibitor Siltuximab, with significant improvement in mental status. Summary of Results: MCD is a rare angiolymphoproliferative disorder of unclear etiology. Most cases occur in middle aged men and are associated with immunosuppression where as SLE is common in women of child bearing age. Reported cases of MCD in association with SLE are common in immunocompetent young women. Our patient is a young woman, HIV/HHV8 negative with good response to Siltuximab, favoring MCD. Conclusions: It is unclear whether this finding of MCD and SLE represents an overlap or a pure association. However, this phenomenon needs further investigation.